Oral manifestations arising from polypharmacy in the elderly of a public shelter in Teresina – Piauí (Research, Society and Development, 2020)
Institutionalized elderly people usually have a different oral condition than the elderly population in general due to the association of several systemic diseases, in addition to poor oral health care. Chronic age-related illnesses, such as dyslipidemia, hypertension, diabetes and depression, usually require the use of multiple drugs, a condition known as polypharmacy. This refers to the use of several medications daily. The present research aimed to verify the oral manifestations in gingiva, gingival ridge, as well as, in the other areas covered by epithelium resulting from polypharmacy in the elderly of a public shelter in Teresina - PI. In this study carried out between October / 2017 to April / 2018, 62 elderly people who met the stipulated inclusion criteria were evaluated, and the participants were institutionalized in a public shelter in Teresina - PI, who had the physical condition to open the oral cavity for the intraoral physical examination. , regardless of sex, education level, social class, who had chronic diseases and who used five or more drugs from different groups on a daily basis, thus characterizing polypharmacy. At the end of the analysis, there were nine elderly people who fit the research standards; they were subclassified according to the degree of the referred pathology and were made aware (patient and caregiver) about the magnitude of the problem and how to ponder and / or remove it. Polypharmacy was present in the entire sample studied and the main manifestations found were: gingival hyperplasia, gingivitis, ulcerations / erythematous areas, lingual coating, dry mouth and candidiasis.